Nutritional composition of boletus mushrooms from Southwest China and their antihyperglycemic and antioxidant activities. (15th November 2016) - Liu, Yuntao; Chen, Di; You, Yuxian; Zeng, Siqi; Li, Yiwen; Tang, Qianqian; Han, Guoquan; Liu, Aiping; Feng, Chaohui; Li, Cheng; Su, Yujie; Su, Zhao; et al.
Highlights: Boletus mushrooms from Southwest China have high protein and low fat contents. These mushrooms accumulate K, Zn, Na, Mg, Cu, Pb, Cd, and As from the soil. Natural habitat had more influence than species on concentration of elements. S . luridus from Sichuan Province showed the highest antioxidant activity. S . luridus from Yunnan Province showed the highest antihyperglycemic activity. Abstract: Thirteen samples representing five species were collected from different provinces of Southwest China, and their chemical composition, antihyperglycemic activity, and antioxidant activity were evaluated. These mushrooms had high crude protein (21.72–30.59 g/100 g dw) and total carbohydrate (49.18–62.58 g/100 g dw) contents, but low crude fat contents (1.96–7.87 g/100 g dw). They also accumulated notable quantities of potassium, zinc, sodium, magnesium and copper from the soil. The potassium content, in particular, was 18.75–39.21 times that found in the soil at the collection site. The natural habitat of these mushrooms, especially the mineral content of the soil, seems to have more influence on the mineral content of these mushrooms than their species. Most of the samples possessed antihyperglycemic and antioxidant activities. Suillellus luridus showed the highest antioxidant activity and antihyperglycemic activities, suggesting that S. luridus shows potential for development as a dietary nutritional supplement.